The role of the economic environment on mortgage defaults during the Great Recession - Sarmiento, Camilo (Routledge Taylor and Francis Group, 2012)
This article shows that the rise in unemployment played a very significant factor in the rise of mortgage delinquencies during the Great Recession. Estimation results, moreover, show that changes in the Unemployment Rate (UR; from loan origination) as opposed to the level of the UR explain mortgage default. Mortgage default is found to be significantly less responsive to declines than to increases in the UR.

Este artículo muestra que el aumento del desempleo jugó un factor muy importante en el aumento de la morosidad hipotecaria durante la Gran Recesión. Además, los resultados de la estimación muestran que los cambios en la Tasa de Desempleo (UR; desde la originación del préstamo) en contraposición al nivel de la UR explican el incumplimiento de las hipotecas. Se ha descubierto que el incumplimiento hipotecario responde significativamente menos a las caídas que a los aumentos en la RU.
Keywords: Recesiones económicas; Crisis económica; Desempleo; Hipotecas; Economic recessions; Economic crisis; Unemployment; Mortgages; Mortgage; Default; Unemployment; Competing risk models